Analisis Pada Pelaku Bisnis Dalam Rekrutmen Karyawan Marketing Digital Di Kabupaten Sumenep - Norsain, Norsain; Pranata, Mohammad Firlie (Aktiva : Jurnal Akuntansi dan Investasi, 2024)
Indonesia has entered the digitalization era, people are starting to trade digitally. The online market is increasingly becoming a big hope for quick profits, shifts from convenience stores to online stores are commonplace for business actors. This is a challenge for businesses to find human resources who can operate computers or can make sales online or what is known as digital marketing. Digital marketing is expected to be able to promote existing products in a business in the digital world with the ability to master the digital market. Sumenep is a city that is geographically located on the eastern tip of Madura Island. Business actors in Sumenep are starting to move towards the online market, which requires digital marketing in their business ventures. The results of the discussion show that it can be concluded from the interviewees that 75% of the business actors in Sumenep Regency are dealing with the online market by retaining old employees and conducting training, while the other 25% is by recruiting new employees.